The Implication of Relationship between Designing Woven Motive Skills and Logical Thinking in Mathematics Learning - Amalia, Rizky; Muchyidin, Arif; Izzati, Nurma (Journal of Mathematical Pedagogy (JoMP), 2019)
This study aims to determine the relationship between the skill of weaving various types of rattan woven motifs with the ability of mathematical logical thinking of students in schools around the Galmantro Rattan Tourism Village of Cirebon Regency. The method used is a quantitative research method with a One-Shot Case Study research design. Data collection techniques used in the form of observation, tests, and questionnaires. The results of this study are (1) during the training, the respondents felt interested in knowing how to weave and the types of woven motifs for rattan crafts because in reality the respondents had never tried directly to weave rattan woven motifs; (2) based on the correlation coefficient test between weaving skills and the mathematical logical thinking test the t and t_table test values are 7.711 more than 2.045, so that the two variables have a significant relationship with the relationship level of 0.599 in the medium category. Keywords: weaving skills, woven motifs, mathematical logical thinking